Oral Corrective Feedback and Learners’ Uptake in Teenage EFL Class - Ivana Ovilia (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This study was done to find out: (1) the types of oral corrective feedback (CF) strategies, (2) the types of learners’ uptake, and (3) the types of learners’ uptake elicited in relation to the teacher’s types of oral CF. In order to answer the research questions, the writer applied two theories, Sheen and Ellis (2011) for oral CF strategies and Panova and Lyster (2002) for the types of learners’ uptake, as the guideline. This study used qualitative approach, using audio recording. The findings showed that there were forty three (43) oral CF occuring in the class, and forty one (41) uptakes elicited in relation to teacher’s oral CF. There were 2 (two) oral CF which did not result in uptake. Six (6) out of nine (9) oral CF strategies and seven (7) out of ten (10) types of learners’ uptake occurred in the class.  Didactic Recast was the most frequently applied oral CF strategies, whereas Repetition was the most frequently applied learners’ uptake type. There were 18 types of oral CF strategies and learners’ uptake sequences occurring in the class, and the most occurring sequence was Didactic Recasts – Repetition, with total 11 times. There were some possible reasons why uptakes did not occur:   learners were taking too long to answer or the teacher did not want to wait longer expecting that learner had already known the correct form through prior explanation. In order to maintain the class running smoothly, the teacher sometimes was faced to a situation when none uptakes were elicited from the learners. Keywords: corrective feedback, oral corrective feedback, uptake